Weakly deformed optical microdisks: A third-order perturbation theory for transverse-magnetic modes. (13th November 2020) - Kullig, Julius; Wiersig, Jan
Abstract: In the past years weakly deformed optical microdisks have become a focus for fundamental and applied research with lots of interesting new findings. A commonly used method to study such cavities is a perturbation theory based on weak boundary deformations (Dubertrand et al 2008 Phys. Rev. A 77, 013 804). In this paper we extent the perturbation theory to the third order which allows us to improve its accuracy significantly. We discuss various example systems in regard of Q -spoiling, frequency splitting, and far-field emission pattern. The results from the perturbation theory are in a very good agreement to full numerical simulations.